LEADER-MEMBER EXCHANGE AMONG MALAYSIAN ARMED FORCES: A DYADIC RELATIONSHIP - Bing, Khuan Wai; Yusoff, Azeman (Management Research Journal, 2019)
Not all leader-member relationships are created equal. The same leader may have very different relationships with each of the individuals with whom he interacts. Those closest to the leader and whom the leader trusted the most are known as the in-group. On the other hand, those whom the leader trusted the least are known as the out-group. The purpose of this preliminary study was to determine the perception of leader-member exchange leadership among Armed Forces personnel in the military. A questionnaire with LMX 7 was distributed to about 200 Armed Forces personnel. The data collected was analyzed descriptively by using mean and percentage. Overall, the quality of relationship between leader and member is positive but only average. The findings also indicated that LMX theory of in-group and out-group appeared not to be applicable in the military setting. However, this finding is not conclusive. Continued LMX studies are needed as this leadership approach addresses a process centered in the interactions between leaders and followers